High-Throughput Genetic Screen Reveals that Early Attachment and Biofilm Formation Are Necessary for Full Pyoverdine Production by Pseudomonas aeruginosa - Kang, Donghoon; Kirienko, Natalia V. (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a re-emerging, multidrug-resistant, opportunistic pathogen that threatens the lives of immunocompromised patients, patients with cystic fibrosis, and those in critical care units. One of the most important virulence factors in this pathogen is the siderophore pyoverdine. Pyoverdine serves several critical roles during infection. Due to its extremely high affinity for ferric iron, pyoverdine gives the pathogen a significant advantage over the host in their competition for iron. In addition, pyoverdine can regulate the production of multiple bacterial virulence factors and perturb host mitochondrial homeostasis. Inhibition of pyoverdine biosynthesis was sufficient to decrease P. aeruginosa pathogenicity in multiple host models. To better understand its regulation, we developed a high-throughput genetic screen that uses the innate fluorescence of pyoverdine to identify genes necessary for its biosynthesis. A substantial number of hits showing severe impairment of pyoverdine production were in genes responsible for early attachment and biofilm formation. In addition to genetic disruption of biofilm, both physical and chemical perturbations also resulted in attenuated pyoverdine production. This regulatory relationship between pyoverdine and biofilm is particularly significant in the context of P. aeruginosa multidrug resistance, where the formation of biofilm is a key mechanism contributing to resistance to antimicrobials and the immune system. Furthermore, we demonstrate that the biofilm inhibitor 2-amino-5,6-dimethylbenzimidazole effectively attenuates pyoverdine production and rescues Caenorhabditis elegans from P. aeruginosa-mediated pathogenesis. Our findings suggest that targeting biofilm formation in P. aeruginosa infections may have multiple therapeutic benefits and that employing an unbiased, systems biology-based approach may be useful for understanding the regulation of specific virulence factors and identifying novel anti-virulence therapeutics or new applications for existing therapies for P. aeruginosa infections.